Wearing face masks when no longer mandatory: An exploratory study about attitudinal and psychological health factors in a large Italian sample - Daniela Di Riso; Silvia Spaggiari; Giulia Calignano; Paola Rigo; Marina Miscioscia (PLoS ONE, 2025)
Throughout the Covid-19 pandemic, face masks emerged as a critical tool to control the virus transmission. While previous studies have investigated the positive and negative attitudes towards the use of face masks when mandatory, our study looks at a different phase: the era of discretionary mask use. Our investigation reached Italian participants (1151), aged 18-64, who underwent an online survey. The study explored the associations between demographic, attitudinal, psychological, and emotional factors that may be involved in the behaviour of wearing a face mask. Then, by using generalized mixed effects models, we explored the predictive role of those factors selected via backward elimination starting from a full model and selecting the model with the best goodness of fit balanced with complexity, and higher explained variance. Specifically, our exploratory study expected that emotional experience aroused by wearing a face mask, negative affectivity, Covid-19-related fear, and anxiety might be significant predictors of face mask wearing. However, only the emotional experience of feeling a sense of care and protected while wearing a face mask, and Covid-19-related fear were significant predictors of face mask-use. We discussed the importance of considering attitudes involved in compliance with healthy behaviours to guide future health interventions.